Father's Attitude In Breastfeeding Support: Literatur Riview - Syamsuri, Prasida Yunita (Sahabat Publikasi Kuu, 2024)
This study aimed to determine the attitudes of fathers in breastfeeding support. Through the application of inclusion and exclusion criteria, this study was a literature review from the last five years, 2019-2024. PubMed and Google Scholar databases were used as data sources, and the publish or perish tool was used to search for publications using the keywords breastfeeding, father support, and father attitudes. An example of a study protocol used by researchers is the Preferred Reporting Items for PRISMA technique. This was a literature review study that used search strategies and inclusion and exclusion criteria. A total of 391 articles were retrieved from PubMed and Google Scholar databases after duplicate records were removed. The selection process involved evaluating the title and abstract, study design, population, and outcomes. Full texts of some articles were accessible. Ultimately, this review contains ten studies. Fathers' attitudes in supporting breastfeeding have a major impact on the achievement of breastfeeding success